A mineral polymer-based two-component inorganic mineral stone paint with magnet tailings as aggregate and a preparation method thereof
Patent Information
- Application Number
- CN202410661266.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-05-27
AI Technical Summary
[0008]本发明实施例的目的在于提供一种以磁铁尾矿为骨料的矿物聚合物基双组份无机真石漆及其制备方法,以解决当前有机乳液真石漆制备原料中骨料供应短缺、价格昂贵,以及真石漆涂层在使用过程中的变色、脏污、粉化、掉砂、掉皮、不耐高温和可燃等真石漆性能有待提高的问题
[0033](1)本发明实施例以磁铁尾矿为真石漆的骨料,对磁铁尾矿进行高附加值利用的同时,一定程度上解决了磁铁尾矿大量长期堆存带来的生态环境问题和安全隐患,缓解了真石漆骨料供应紧缺,价格昂贵的问题;此外,以粉煤灰和水玻璃聚合制备矿物聚合物基料以代替传统真石漆的有机乳液基料,不仅改进了传统真石漆的某些主要性能,而且极大降低了真石漆的生产成本。
Smart Images

Figure CN118421118B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of stone paint preparation technology, and in particular relates to a mineral polymer-based two-component inorganic stone paint with magnetite tailings as aggregate and its preparation method. Background Technology
[0002] Typically, stone-like paint is refined from synthetic resin emulsions, coarse and fine aggregates, fillers, and additives, providing buildings with a three-dimensional decorative effect and unique texture reminiscent of natural stone. The emulsion is the film-forming substance, exhibiting good film-forming properties and good storage stability; therefore, most stone-like paints on the market currently use emulsions as their film-forming substance. However, the commonly used emulsion film-forming substances have drawbacks during use, including discoloration, soiling, chalking, sand shedding, peeling, poor high-temperature resistance, and flammability, requiring further improvement.
[0003] Inorganic stone-like paint is a new type of building coating material developed using scientific methods with inorganic mineral polymers as the base material. It possesses excellent properties such as strong adhesion, strong corrosion resistance, high temperature resistance, heat insulation, and flame retardancy. While providing decorative effects for building exteriors, it also achieves thermal insulation, energy saving, high temperature resistance, and flame retardancy, thereby reducing building energy consumption, alleviating energy shortages, and improving building safety. However, single-component stone-like paint using inorganic mineral polymers as the film-forming substance has relatively poor storage stability and is not suitable for long-term storage. Two-component inorganic stone-like paint, on the other hand, separates the two components during the production process and mixes them evenly on-site before use, completely solving the problem of poor storage stability of inorganic polymer-based stone-like paint.
[0004] Sand is divided into natural sand and manufactured sand: the mining of natural sand and gravel is regulated due to the damage to the ecological environment; manufactured sand is obtained by removing soil from natural stone, mechanically crushing and screening, and its supply is scarce and its manufacturing cost is high; the current situation of sand to some extent limits the widespread application of real stone paint.
[0005] Magnetite tailings are waste generated during the beneficiation process of iron ore mining enterprises. my country has a vast quantity of magnetite tailings, which not only occupy a large amount of public resources but also pose serious safety hazards, incur high maintenance costs, and limit enterprise production capacity. Therefore, there is an urgent need to find efficient and comprehensive utilization solutions for magnetite tailings. Physicochemical property testing of magnetite tailings revealed that its main mineral composition is quartz, similar to natural sand. Therefore, it is screened to obtain tailings sand of different particle sizes, which, after scientific grading, can be used as aggregate for stone paint, replacing the scarce natural sand and thus reducing the production cost of stone paint. At the same time, it can also reduce the accumulation of magnetite tailings and the resulting ecological and environmental problems to a certain extent.
[0006] Currently, most stone-like paints on the market use organic emulsion film-forming substances, which have the disadvantage of short lifespan in terms of aging resistance, weather resistance, and stain resistance. After the coating is exposed to the environment for a period of time, it will show phenomena such as discoloration, dirt, chalking, sand shedding, and peeling, which seriously affects the decorative and beautifying effect of the stone-like paint coating on buildings. Moreover, its poor high temperature resistance and flame retardancy greatly limit its application in high-temperature environments, such as industrial kilns and pipelines.
[0007] In summary, there is an urgent need to address the current shortage and high price of aggregates in the raw materials for preparing stone-like paint, as well as the need to improve the performance of stone-like paint coatings during use, such as discoloration, dirt, chalking, sand shedding, peeling, poor high-temperature resistance, and flammability. Summary of the Invention
[0008] The purpose of this invention is to provide a mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate and its preparation method, thereby addressing the current problems of aggregate shortage and high price in the preparation of organic emulsion stone-like paints, as well as the need to improve the performance of stone-like paints during use, such as discoloration, dirt accumulation, chalking, sand shedding, peeling, poor high-temperature resistance, and flammability. It also solves the problem of poor storage stability and unsuitability for long-term preservation of inorganic stone-like paints.
[0009] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is a mineral polymer-based two-component inorganic stone paint using magnetite tailings as aggregate, comprising the following components and their mass fractions:
[0010]
[0011] Furthermore, the particle size of magnetite tailings I is 20 mesh to 40 mesh; the particle size of magnetite tailings II is 40 mesh to 80 mesh; and the particle size of magnetite tailings III is 80 mesh to 120 mesh.
[0012] Furthermore, the mineral polymer matrix is prepared by reacting water glass and fly ash in a mass ratio of (1.0 to 1.2):1.
[0013] Furthermore, the fly ash is ground to 800-1000 mesh after impurity removal and grinding; the water glass is industrial water glass mixed with a 40% sodium hydroxide solution to a modulus of 1.6-1.9.
[0014] Furthermore, the cellulose is hydroxypropyl methylcellulose with a viscosity of 150,000 to 200,000 and a particle size of 100 to 150 mesh.
[0015] Furthermore, the functional additive comprises the following components and their mass fractions:
[0016] 1.5 to 2.3 parts wetting agent;
[0017] 2.5 to 3.6 parts of defoamer;
[0018] Antifreeze 1.3 to 2.2 parts.
[0019] Furthermore, the wetting agent includes X-405; the defoamer includes NXZ; and the antifreeze agent includes ethylene glycol.
[0020] This invention also provides a method for preparing a mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate, comprising the following steps:
[0021] Step S1: Screen the magnetite tailings and use them as aggregate for real stone paint for later use;
[0022] Step S2: Sieve the fly ash to remove impurities, grind it, and set it aside for later use;
[0023] Step S3: First, add magnetite tailings III and fly ash to the mixer according to the ratio and mix. Then add hydroxypropyl methylcellulose and mix. Next, add magnetite tailings II and mix. Finally, add magnetite tailings I and mix to obtain component A.
[0024] Step S4: Add water glass and sodium hydroxide solution to a disperser according to the ratio, stir and disperse, and then add functional additives: defoamer, wetting agent and antifreeze to obtain component B;
[0025] Step S5: Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A, stir and mix, and finally add component B, stir and mix to obtain mineral polymer-based inorganic stone paint.
[0026] This invention also provides a method for preparing a mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate, comprising the following steps:
[0027] Step S1: Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0028] Step S2: Sieve the fly ash to remove impurities, and grind it to obtain 800-1000 mesh fly ash for later use;
[0029] Step S3: First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 300-400 r / min for 15-20 min. Then add hydroxypropyl methylcellulose and mix for 8-10 min. Next, add magnetite tailings II and mix at 100-200 r / min for 12-15 min. Finally, add magnetite tailings I and mix at 100-200 r / min for 15-18 min to obtain component A.
[0030] Step S4: Add water glass and sodium hydroxide solution to a disperser according to the ratio, and stir and disperse at 800-1000 r / min for 15-18 min. Then add functional additives: defoamer, wetting agent and antifreeze agent respectively. Disperse at 800-1000 r / min for 5-7 min after each addition to obtain component B.
[0031] Step S5: Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. First, stir and mix at 100-200 r / min for 10-12 min, then mix at 300-400 r / min for 15-17 min. Finally, add component B, first stir and mix at 300-400 r / min for 20-23 min, then mix at 700-800 r / min for 15-20 min to obtain mineral polymer-based inorganic stone paint.
[0032] The beneficial effects of this invention are:
[0033] (1) In this embodiment of the invention, magnetite tailings are used as aggregate for real stone paint. While making high-value-added use of magnetite tailings, the ecological and environmental problems and safety hazards caused by the long-term stockpiling of large quantities of magnetite tailings are solved to a certain extent, and the problem of tight supply and high price of real stone paint aggregate is alleviated. In addition, mineral polymer base material prepared by polymerizing fly ash and water glass to replace the organic emulsion base material of traditional real stone paint not only improves some of the main properties of traditional real stone paint, but also greatly reduces the production cost of real stone paint.
[0034] (2) The embodiments of the present invention use mineral inorganic polymer as base material and magnetite tailings of different particle sizes as aggregate. The resulting mineral polymer-based two-component inorganic real stone paint coating has excellent bonding strength, water resistance, stain resistance and weather resistance.
[0035] (3) In the embodiments of the present invention, mineral inorganic polymer is used as base material and magnetite tailings of different particle sizes are used as aggregate. During the film formation process, the mineral polymer base material can form chemical bonds with the aggregate and substrate. The bonding force is much greater than the bonding force between the emulsion film and the aggregate and substrate. This can solve the problems of sand shedding, poor adhesion to the substrate, easy peeling, poor high temperature resistance and flammability of the emulsion-based stone paint coating.
[0036] (4) In this embodiment of the invention, mineral inorganic polymers are used as the base material and magnetite tailings of different particle sizes are used as aggregates. During the film-forming process of the base material, since the magnetite tailings aggregate and building substrate contain quartz and aluminum-containing minerals, they can undergo polymerization and cross-linking with some of the silicon and aluminum on their surface to form an inorganic network structure, thereby greatly enhancing the adhesion and preventing the stone paint from prematurely peeling off from the stone paint coating and peeling off from the substrate due to environmental erosion during use. Due to the chemical bonding between the components of the mineral inorganic stone paint, it has excellent weather resistance, stain resistance and aging resistance, which can eliminate the traditional stone paint topcoat application process, thereby reducing costs.
[0037] (5) The embodiments of the present invention adopt a two-component, on-site mixing and construction method, which can solve the problem that the raw materials of mineral polymer inorganic base material are prone to polymerization when mixed and cannot be stored for a long time, thus ensuring the excellent film-forming performance of mineral polymer base material for real stone paint coating. Attached Figure Description
[0038] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0039] Figure 1 This is a flowchart of the inorganic stone paint preparation process according to an embodiment of the present invention.
[0040] Figure 2 This is the XRD diffraction pattern of magnetite tailings according to an embodiment of the present invention. Detailed Implementation
[0041] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0042] This invention provides a mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate, comprising the following components and parts by weight:
[0043]
[0044] Among them, the mesh size of magnetite tailings I is 20 to 40 mesh; the mesh size of magnetite tailings II is 40 to 80 mesh; and the mesh size of magnetite tailings III is greater than 80 to 120 mesh.
[0045] The magnetite tailings used in this invention, after radionuclide activity testing, belong to Class A decorative materials and their use is unrestricted. For example... Figure 2 The XRD diffraction pattern of the magnetite tailings shown indicates that its main mineral components include siderite, quartz, muscovite, barite, and pyrite, with main chemical components such as SiO2, CaO, Fe2O3, and Al2O3. Screening of the magnetite tailings yielded tailings sand with three particle size ranges. A reasonable gradation of these three types, combined with other functional additives, was used to prepare a mineral polymer inorganic stone-like paint. This approach reduces the hazards caused by large-scale accumulation of magnetite tailings in mining areas, lowers the cost of the stone-like paint, solves problems encountered during coating and application, and expands its application.
[0046] The mineral polymer base is prepared by reacting water glass and fly ash in a mass ratio of 1.0 to 1.2. The fly ash is ground to 800 to 1000 mesh after impurity removal and grinding; the water glass is industrial water glass mixed with a 40% sodium hydroxide solution to a modulus of 1.6 to 1.9.
[0047] The cellulose is hydroxypropyl methylcellulose (HPMC), with a viscosity of 150,000–200,000 and a particle size of 100–150 mesh; the functional additives include the following components and their mass fractions:
[0048] 1.5 to 2.3 parts wetting agent;
[0049] 2.5 to 3.6 parts of defoamer;
[0050] Antifreeze: 1.3 to 2.2 parts;
[0051] The wetting agent includes X-405; the defoamer includes NXZ; and the antifreeze agent includes ethylene glycol.
[0052] See Figure 1 The present invention also provides a method for preparing a mineral polymer-based two-component inorganic stone paint using magnetite tailings as aggregate, comprising the following steps:
[0053] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0054] S2. Sieve the fly ash to remove impurities, and grind it to obtain 800-1000 mesh fly ash for later use;
[0055] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 300-400 r / min for 15-20 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 8-10 min. Next, add magnetite tailings II and mix at 100-200 r / min for 12-15 min. Finally, add magnetite tailings I and mix at 100-200 r / min for 15-18 min to obtain component A.
[0056] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, and stir and disperse at 800-1000 r / min for 15-18 min. Then add functional additives: defoamer, wetting agent and antifreeze. Disperse at 800-1000 r / min for 5-7 min after each addition to obtain component B.
[0057] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. Mix at 100-200 rpm for 10-12 minutes, then at 300-400 rpm for 15-17 minutes. Finally, add component B and mix at 300-400 rpm for 20-23 minutes, then at 700-800 rpm for 15-20 minutes to obtain the mineral polymer-based inorganic stone paint. (The purpose of adding deionized water is to adjust the viscosity of the stone paint. The reason for gradually increasing the mixing speed is that component A is a powder, and mixing too quickly at the beginning will generate a lot of dust. Therefore, the mixing speed is gradually increased.)
[0058] In this invention, during the reaction of water glass and fly ash to form an inorganic mineral polymer film-forming substance, the strong alkalinity of water glass allows it to react with the siderite and pyrite on the surface of magnetite tailings particles to form a trisodium hexahydroxyferrate complex. The silicon and aluminum components in the quartz and mica on the surface of the magnetite tailings particles can be partially activated in the alkaline environment and participate in the macromolecular network of the mineral inorganic polymer matrix, thereby greatly enhancing the coating's adhesion strength, stain resistance, and weather resistance through chemical bonding. Barite in magnetite tailings is an excellent filler that can greatly increase the coating's thickness, strength, and durability. Simultaneously, barite acts as a mineralizer, enhancing the coating's early and later strength. Furthermore, the mineral polymer is composed of silicon-oxygen tetrahedra and aluminum-oxygen tetrahedra linked by a shared oxygen atom. Some cations in magnetite tailings, such as Na... + K + Ca 2+ Ba 2+ Mg 2+ Al, etc., exists in the cavity of the three-dimensional network structure to balance IV coordination. 3+ The negative charge, the mineral inorganic polymer matrix is mainly covalently bonded (similar to ceramics). It is precisely because of these unique components in magnetite tailings that... Figure 2 During the formation of the mineral-inorganic polymer film-forming material, different levels of participation in the reaction result in the prepared coating having excellent performance.
[0059] This invention provides a mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate, the formulation of which is shown in Table 1:
[0060] Table 1. Formulation of a two-component inorganic stone-like paint based on a mineral polymer as aggregate, using magnetite tailings (parts by mass).
[0061]
[0062] Continued from Table 1: Formulation of a two-component inorganic stone-like paint based on a mineral polymer with magnetite tailings as aggregate (parts by mass).
[0063]
[0064]
[0065] Example 1
[0066] A mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate is prepared according to Formula 1, comprising the following steps:
[0067] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0068] S2. Sieve the fly ash to remove impurities, grind it to obtain 800-mesh fly ash, and set it aside;
[0069] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 300 r / min for 15 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 8 min. Next, add magnetite tailings II and mix at 100 r / min for 12 min. Finally, add magnetite tailings I and mix at 100 r / min for 15 min to obtain component A.
[0070] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, stir and disperse at 800 r / min for 15 min, then add functional additives: defoamer, wetting agent and antifreeze, and disperse at 800 r / min for 5 min after each addition to obtain component B;
[0071] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. First, mix at 100 r / min for 10 min, then mix at 300 r / min for 15 min. Finally, add component B, first mix at 300 r / min for 20 min, then mix at 700 r / min for 15 min to obtain mineral polymer-based inorganic stone paint.
[0072] Example 2
[0073] A mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate was prepared according to Formula 2, comprising the following steps:
[0074] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0075] S2. Sieve the fly ash to remove impurities, grind it to obtain 1000-mesh fly ash, and set it aside;
[0076] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 400 r / min for 20 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 10 min. Next, add magnetite tailings II and mix at 200 r / min for 15 min. Finally, add magnetite tailings I and mix at 200 r / min for 18 min to obtain component A.
[0077] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, stir and disperse at 1000 r / min for 18 min, then add functional additives: defoamer, wetting agent and antifreeze, and disperse at 1000 r / min for 7 min after each addition to obtain component B;
[0078] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. Mix at 200 r / min for 12 min, then at 400 r / min for 17 min. Finally, add component B, mix at 400 r / min for 23 min, then at 800 r / min for 20 min to obtain mineral polymer-based inorganic stone paint.
[0079] Example 3
[0080] A mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate was prepared according to Formula 3, comprising the following steps:
[0081] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0082] S2. Sieve the fly ash to remove impurities, grind it to obtain 900-mesh fly ash, and set it aside;
[0083] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 350 r / min for 18 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 9 min. Next, add magnetite tailings II and mix at 150 r / min for 13 min. Finally, add magnetite tailings I and mix at 150 r / min for 17 min to obtain component A.
[0084] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, stir and disperse at 900 r / min for 17 min, then add functional additives: defoamer, wetting agent and antifreeze, and disperse at 900 r / min for 6 min after each addition to obtain component B;
[0085] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. First, mix at 150 r / min for 11 min, then mix at 350 r / min for 16 min. Finally, add component B, first mix at 350 r / min for 21 min, then mix at 750 r / min for 18 min to obtain mineral polymer-based inorganic stone paint.
[0086] Example 4
[0087] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0088] S2. Sieve the fly ash to remove impurities, grind it to obtain 800-mesh fly ash, and set it aside;
[0089] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 300 r / min for 20 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 10 min. Next, add magnetite tailings II and mix at 100 r / min for 15 min. Finally, add magnetite tailings I and mix at 100 r / min for 18 min to obtain component A.
[0090] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, stir and disperse at 800 r / min for 18 min, then add functional additives: defoamer, wetting agent and antifreeze, and disperse at 800 r / min for 7 min after each addition to obtain component B;
[0091] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. Mix at 100 r / min for 12 min, then mix at 300 r / min for 17 min. Finally, add component B, mix at 300 r / min for 23 min, then mix at 700 r / min for 20 min to obtain mineral polymer-based inorganic stone paint.
[0092] Example 5
[0093] Formula 5 is used to prepare a mineral polymer-based two-component inorganic stone-like paint with magnetite tailings as aggregate, comprising the following steps:
[0094] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0095] S2. Sieve the fly ash to remove impurities, grind it to obtain 1000-mesh fly ash, and set it aside;
[0096] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 400 r / min for 15 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 8 min. Next, add magnetite tailings II and mix at 200 r / min for 15 min. Finally, add magnetite tailings I and mix at 200 r / min for 15 min to obtain component A.
[0097] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, stir and disperse at 1000 r / min for 15 min, then add functional additives: defoamer, wetting agent and antifreeze, and disperse at 1000 r / min for 5 min after each addition to obtain component B;
[0098] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. Mix at 200 r / min for 10 min, then at 400 r / min for 15 min. Finally, add component B, mix at 400 r / min for 20 min, then at 800 r / min for 15 min to obtain mineral polymer-based inorganic stone paint.
[0099] Comparative Example 1
[0100] A mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate was prepared according to the formulation of Comparative Example 1, comprising the following steps:
[0101] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0102] S2. Sieve the fly ash to remove impurities, grind it to obtain 900-mesh fly ash, and set it aside;
[0103] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 350 r / min for 18 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 9 min. Next, add magnetite tailings II and mix at 150 r / min for 13 min. Finally, add magnetite tailings I and mix at 150 r / min for 17 min to obtain component A.
[0104] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, stir and disperse at 900 r / min for 17 min, then add functional additives: defoamer, wetting agent and antifreeze, and disperse at 900 r / min for 6 min after each addition to obtain component B;
[0105] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. First, mix at 150 r / min for 11 min, then mix at 350 r / min for 16 min. Finally, add component B, first mix at 350 r / min for 21 min, then mix at 750 r / min for 18 min to obtain mineral polymer-based inorganic stone paint.
[0106] Comparative Example 2
[0107] A mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate was prepared according to the formulation of Comparative Example 2, comprising the following steps:
[0108] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0109] S2. Sieve the fly ash to remove impurities, grind it to obtain 900-mesh fly ash, and set it aside;
[0110] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 350 r / min for 18 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 9 min. Next, add magnetite tailings II and mix at 150 r / min for 13 min. Finally, add magnetite tailings I and mix at 150 r / min for 17 min to obtain component A.
[0111] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, stir and disperse at 900 r / min for 17 min, then add functional additives: defoamer, wetting agent and antifreeze, and disperse at 900 r / min for 6 min after each addition to obtain component B;
[0112] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. First, mix at 150 r / min for 11 min, then mix at 350 r / min for 16 min. Finally, add component B, first mix at 350 r / min for 21 min, then mix at 750 r / min for 18 min to obtain mineral polymer-based inorganic stone paint.
[0113] Comparative Example 3
[0114] A type of stone-like paint using magnetite tailings as aggregate
[0115] Except that the film-forming substance is pure acrylic emulsion, and the dosage is in accordance with national standards (34 parts), and 1.3 parts of film-forming aid are added, the preparation process is carried out according to conventional processes. The specific formula and process steps are as follows:
[0116] Formula (parts by weight):
[0117]
[0118] Process steps: S1: Add 1 / 2 of the mass of the defoamer and wetting agent to 3 / 4 of the mass of deionized water, and stir and disperse at a speed of 700 r / min to 1000 r / min for 3 min to 10 min to obtain liquid A;
[0119] S2: Add the emulsion and film-forming aid to 1 / 4 of the mass of deionized water, and stir and disperse at a speed of 400 r / min to 800 r / min for 3 min to 10 min to obtain liquid B;
[0120] S3: Add the specified mass fractions of magnetite tailings III, magnetite tailings II, and magnetite tailings I sequentially to liquid A, and disperse them at a rotation speed of 500 r / min to 700 r / min for 4 min to 8 min respectively to obtain liquid C;
[0121] S4: Add half the mass of the defoamer, the mass of ethylene glycol and hydroxypropyl methylcellulose to the liquid C in sequence, disperse at a speed of 800 r / min to 1200 r / min for 6 min to 10 min, then add the liquid B, disperse at a speed of 500 r / min to 700 r / min for 4 min to 8 min to obtain liquid D;
[0122] S5: Adjust the pH value of the material solution D to between 7 and 9, then disperse it at a speed of 1000 r / min to 1500 r / min for 4 min to 8 min, and finally disperse it at a speed of 400 r / min to 600 r / min for 8 min to 15 min to obtain the real stone paint of the magnetite tailings.
[0123] Comparative Example 4
[0124] A type of stone-like paint using magnetite tailings as aggregate
[0125] Except that the film-forming substance is a styrene-acrylic emulsion, and the dosage is in accordance with national standards (34 parts), and 1.3 parts of film-forming aid are added, the preparation process is carried out according to conventional processes. The specific formula and process steps are as follows:
[0126] Formula (parts by weight):
[0127]
[0128]
[0129] Process steps:
[0130] S1: Add 1 / 2 of the stated mass of defoamer and wetting agent to 3 / 4 of the mass of deionized water, and stir and disperse at a speed of 700 r / min to 1000 r / min for 3 min to 10 min to obtain liquid A;
[0131] S2: Add the emulsion and film-forming aid to 1 / 4 of the mass of deionized water, and stir and disperse at a speed of 400 r / min to 800 r / min for 3 min to 10 min to obtain liquid B;
[0132] S3: Add the specified mass fractions of magnetite tailings III, magnetite tailings II, and magnetite tailings I sequentially to liquid A, and disperse them at a rotation speed of 500 r / min to 700 r / min for 4 min to 8 min respectively to obtain liquid C;
[0133] S4: Add half the mass of the defoamer, the mass of ethylene glycol and hydroxypropyl methylcellulose to the liquid C in sequence, disperse at a speed of 800 r / min to 1200 r / min for 6 min to 10 min, then add the liquid B, disperse at a speed of 500 r / min to 700 r / min for 4 min to 8 min to obtain liquid D;
[0134] S5: Adjust the pH value of the material solution D to between 7 and 9, then disperse it at a speed of 1000 r / min to 1500 r / min for 4 min to 8 min, and finally disperse it at a speed of 400 r / min to 600 r / min for 8 min to 15 min to obtain the real stone paint of the magnetite tailings.
[0135] Comparative Example 5
[0136] A mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate was prepared according to the formulation of Comparative Example 5, including the following steps:
[0137] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0138] S2. Sieve the fly ash to remove impurities, grind it to obtain 900-mesh fly ash, and set it aside;
[0139] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 350 r / min for 18 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 9 min. Next, add magnetite tailings II and mix at 150 r / min for 13 min. Finally, add magnetite tailings I and mix at 150 r / min for 17 min to obtain component A.
[0140] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, stir and disperse at 900 r / min for 17 min, then add functional additives: defoamer, wetting agent and antifreeze, and disperse at 900 r / min for 6 min after each addition to obtain component B;
[0141] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. First, mix at 150 r / min for 11 min, then mix at 350 r / min for 16 min. Finally, add component B, first mix at 350 r / min for 21 min, then mix at 750 r / min for 18 min to obtain mineral polymer-based inorganic stone paint.
[0142] Comparative Example 6
[0143] A mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate was prepared according to the formulation of Comparative Example 6, comprising the following steps:
[0144] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0145] S2. Sieve the fly ash to remove impurities, grind it to obtain 900-mesh fly ash, and set it aside;
[0146] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 350 r / min for 18 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 9 min. Next, add magnetite tailings II and mix at 150 r / min for 13 min. Finally, add magnetite tailings I and mix at 150 r / min for 17 min to obtain component A.
[0147] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, stir and disperse at 900 r / min for 17 min, then add functional additives: defoamer, wetting agent and antifreeze, and disperse at 900 r / min for 6 min after each addition to obtain component B;
[0148] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. First, mix at 150 r / min for 11 min, then mix at 350 r / min for 16 min. Finally, add component B, first mix at 350 r / min for 21 min, then mix at 750 r / min for 18 min to obtain mineral polymer-based inorganic stone paint.
[0149] Comparative Example 7
[0150] A two-component inorganic stone-like paint based on a mineral polymer, using magnetite tailings as aggregate, was prepared according to the formulation of Comparative Example 7, comprising the following steps:
[0151] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0152] S2. Sieve the fly ash to remove impurities, grind it to obtain 900-mesh fly ash, and set it aside;
[0153] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 350 r / min for 18 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 9 min. Next, add magnetite tailings II and mix at 150 r / min for 13 min. Finally, add magnetite tailings I and mix at 150 r / min for 17 min to obtain component A.
[0154] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, stir and disperse at 900 r / min for 17 min, then add functional additives: defoamer, wetting agent and antifreeze, and disperse at 900 r / min for 6 min after each addition to obtain component B;
[0155] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. First, mix at 150 r / min for 11 min, then mix at 350 r / min for 16 min. Finally, add component B, first mix at 350 r / min for 21 min, then mix at 750 r / min for 18 min to obtain mineral polymer-based inorganic stone paint.
[0156] Comparative Example 8
[0157] A mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate was prepared according to the formulation of Comparative Example 8, including the following steps:
[0158] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0159] S2. Sieve the fly ash to remove impurities, grind it to obtain 900-mesh fly ash, and set it aside;
[0160] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 350 r / min for 18 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 9 min. Next, add magnetite tailings II and mix at 150 r / min for 13 min. Finally, add magnetite tailings I and mix at 150 r / min for 17 min to obtain component A.
[0161] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, stir and disperse at 900 r / min for 17 min, then add functional additives: defoamer, wetting agent and antifreeze, and disperse at 900 r / min for 6 min after each addition to obtain component B;
[0162] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. First, mix at 150 r / min for 11 min, then mix at 350 r / min for 16 min. Finally, add component B, first mix at 350 r / min for 21 min, then mix at 750 r / min for 18 min to obtain mineral polymer-based inorganic stone paint.
[0163] Comparative Example 9
[0164] A mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate was prepared according to the formulation of Comparative Example 9, comprising the following steps:
[0165] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0166] S2. Sieve the fly ash to remove impurities, grind it to obtain 900-mesh fly ash, and set it aside;
[0167] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 350 r / min for 18 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 9 min. Next, add magnetite tailings II and mix at 150 r / min for 13 min. Finally, add magnetite tailings I and mix at 150 r / min for 17 min to obtain component A.
[0168] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, stir and disperse at 900 r / min for 17 min, then add functional additives: defoamer, wetting agent and antifreeze, and disperse at 900 r / min for 6 min after each addition to obtain component B;
[0169] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. First, mix at 150 r / min for 11 min, then mix at 350 r / min for 16 min. Finally, add component B, first mix at 350 r / min for 21 min, then mix at 750 r / min for 18 min to obtain mineral polymer-based inorganic stone paint.
[0170] Comparative Example 10
[0171] A mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate was prepared according to the formulation of Comparative Example 10, including the following steps:
[0172] S1. Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use.
[0173] S2. Sieve the fly ash to remove impurities, grind it to obtain 900-mesh fly ash, and set it aside;
[0174] S3. First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 350 r / min for 18 min. Then add hydroxypropyl methylcellulose (HPMC) and mix for 9 min. Next, add magnetite tailings II and mix at 150 r / min for 13 min. Finally, add magnetite tailings I and mix at 150 r / min for 17 min to obtain component A.
[0175] S4. Add water glass and sodium hydroxide solution to a high-speed disperser according to the ratio, stir and disperse at 900 r / min for 17 min, then add functional additives: defoamer, wetting agent and antifreeze, and disperse at 900 r / min for 6 min after each addition to obtain component B;
[0176] S5. Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. First, mix at 150 r / min for 11 min, then mix at 350 r / min for 16 min. Finally, add component B, first mix at 350 r / min for 21 min, then mix at 750 r / min for 18 min to obtain mineral polymer-based inorganic stone paint.
[0177] Experimental Example
[0178] The performance of the mineral polymer-based two-component inorganic stone paint with magnetite tailings as aggregate prepared in Examples 1-5 of this invention and the stone paint products prepared in Comparative Examples 1-10 were tested, and the test results are shown in Table 2.
[0179] Table 2. Performance test results of the stone-like paint prepared in the embodiments and comparative examples of the present invention.
[0180]
[0181]
[0182]
[0183] Table 2 (Continued) shows the performance test results of the real stone paint prepared in the embodiments and comparative examples of the present invention.
[0184]
[0185] Table 2 shows that the real stone paint and its coatings prepared in Examples 1-5 all met the requirements of the building industry standards and exhibited superior performance, with Example 3 showing the best performance. However, the real stone paint coatings prepared in Comparative Examples 1-4 did not meet the requirements of the building industry standards in some aspects, particularly in terms of adhesion strength, stain resistance, artificial aging resistance, heat resistance, and flame retardancy, all of which deteriorated significantly. Comparative Examples 5-10 mainly verified the effects of different types and amounts of wetting agents, defoamers, and antifreeze agents; the real stone paint coatings prepared in these examples did not meet the requirements of the building industry standards in some aspects. Therefore, the inorganic mineral polymer film-forming material prepared by this invention using fly ash and water glass as raw materials ensures the excellent performance of the real stone paint. In particular, due to the strong chemical bonding between the inorganic polymer base material and the magnetite tailings aggregate and substrate during the film-forming process, the adhesion of the coating is greatly enhanced, thereby improving the defects of stone paint such as sand shedding, peeling, poor stain resistance and aging resistance during use; inorganic stone paint prepared with tailings as aggregate and inorganic mineral polymer as film-forming material has excellent temperature resistance and flame retardancy; due to the advantages of the stone paint, the process of applying topcoat can be eliminated, which greatly saves costs and labor.
[0186] The various embodiments in this specification are described in a related manner. Similar or identical parts between embodiments can be referred to mutually. Each embodiment focuses on describing the differences from other embodiments. In particular, the system embodiments are basically similar to the method embodiments, so the description is relatively simple; relevant parts can be referred to the descriptions of the method embodiments.
[0187] The above description is merely a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are included within the scope of protection of the present invention.
Claims
1. A method for preparing a mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate, characterized in that, The raw materials and their weight percentages in the mineral polymer-based two-component inorganic stone-like paint are as follows: 70-78 parts of mineral polymer base; Magnetite tailings I, 40-49 parts; Magnetite tailings II, 75-84 parts; Magnetite tailings III, 33-46 parts; 6 to 10 parts of hydroxypropyl methylcellulose; Functional additives: 5.3 to 8.1 parts; 12 to 20 parts deionized water; The particle size of magnetite tailings I is 20-40 mesh; the particle size of magnetite tailings II is 40-80 mesh; and the particle size of magnetite tailings III is 80-120 mesh. The functional additive comprises the following components and parts by weight: 1.5 to 2.3 parts wetting agent, 2.5 to 3.6 parts defoamer, and 1.3 to 2.2 parts antifreeze; the wetting agent is X-405; the defoamer is NXZ; and the antifreeze is ethylene glycol. The preparation method of the mineral polymer-based two-component inorganic stone paint is as follows: Step S1: Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use. Step S2: Sieve the fly ash to remove impurities, grind it, and set it aside for later use; Step S3: First, add magnetite tailings III and fly ash to the mixer according to the ratio and mix. Then add hydroxypropyl methylcellulose and mix. Next, add magnetite tailings II and mix. Finally, add magnetite tailings I and mix to obtain component A. Step S4: Add industrial water glass and sodium hydroxide solution to a disperser according to the ratio, stir and disperse, and then add functional additives, including defoamer, wetting agent and antifreeze, to obtain component B; Step S5: Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A, stir and mix, and finally add component B, stir and mix to obtain mineral polymer-based two-component inorganic stone paint. The mineral polymer base material is prepared by reacting water glass and fly ash in a mass ratio of (1.0~1.2):
1. The fly ash is ground to 800-1000 mesh after impurity removal and grinding; the water glass is industrial water glass mixed with a 40% sodium hydroxide solution to a modulus of 1.6-1.
9.
2. The method for preparing a mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate according to claim 1, characterized in that, The hydroxypropyl methylcellulose has a viscosity of 150,000 to 200,000 and a particle size of 100 to 150 mesh.
3. A method for preparing a mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate according to any one of claims 1 to 2, characterized in that, Includes the following steps: Step S1: Screen the magnetite tailings to obtain magnetite tailings I, magnetite tailings II and magnetite tailings III, which will be used as aggregates for real stone paint for later use. Step S2: Sieve the fly ash to remove impurities, and grind it to obtain 800~1000 mesh fly ash for later use; Step S3: First, add magnetite tailings III and fly ash to a horizontal dry powder coating mixer according to the ratio, and mix at 300~400 r / min for 15~20 min. Then add hydroxypropyl methylcellulose and mix for 8~10 min. Next, add magnetite tailings II and mix at 100~200 r / min for 12~15 min. Finally, add magnetite tailings I and mix at 100~200 r / min for 15~18 min to obtain component A. Step S4: Add industrial water glass and sodium hydroxide solution to a disperser according to the ratio, stir and disperse at 800~1000 r / min for 15~18 min, and then add functional additives, including defoamer, wetting agent and antifreeze agent respectively. Disperse each additive at 800~1000 r / min for 5~7 min to obtain component B. Step S5: Add deionized water to the horizontal stone paint mixer according to the ratio, then add component A. First, stir and mix at 100~200 r / min for 10~12 min, then mix at 300~400 r / min for 15~17 min. Finally, add component B, first stir and mix at 300~400 r / min for 20~23 min, then mix at 700~800 r / min for 15~20 min to obtain a mineral polymer-based two-component inorganic stone paint.
4. A mineral polymer-based two-component inorganic stone-like paint using magnetite tailings as aggregate, characterized in that, The mineral polymer-based two-component inorganic stone paint, prepared by the preparation method according to any one of claims 1 to 2, comprises the following raw materials and their mass fractions: 70-78 parts of mineral polymer base; Magnetite tailings I, 40-49 parts; Magnetite tailings II, 75-84 parts; Magnetite tailings III, 33-46 parts; 6 to 10 parts of hydroxypropyl methylcellulose; Functional additives: 5.3 to 8.1 parts; 12 to 20 parts deionized water.
Citation Information
Patent Citations
An inorganic coating using geopolymer materials as film-forming substances
CN102276229A
Tailing mud aggregate inorganic real stone paint and preparation method thereof
CN116730671A